PENGARUH KECERDASAN EMOSIONAL DAN DIGITAL SKILLS TERHADAP KESIAPAN KERJA PADA MAHASISWA S1 TELKOM UNIVERSITY ANGKATAN 2018 - Elva Elviana; Kiki Sudiana (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
This study aims to determine the effect of emotional intelligence and digital skills partially and simultaneously on work readiness of Telkom University Undergraduate Students Class of 2018. The method used in this research is a quantitative method, with collecting data by distributing questionnaires to 375 respondents. Sampling using probability sampling method with the type of proportionate stratified random sampling. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of the study show that emotional intelligence and digital skills partially have a positive and significant effect on work readiness. Emotional intelligence and digital skills simultaneously have a positive and significant effect on job readiness by 23.8% and the remaining 76.2% are influenced by other variables not examined in this study.